2023
DOI: 10.3389/fspor.2023.1260942
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sport practice to improve balance control of visually impaired individuals: a narrative review with future perspectives

Giuditta Carretti,
Mirko Manetti,
Mirca Marini

Abstract: Visual disability negatively impacts balance, everyday self-efficacy, and mobility and often leads affected subjects to perceive physical exercise as a burdensome challenge thus discouraging them from practicing. Despite the well-proven benefits of regular physical activity in visually impaired people, especially addressing postural control, there are no specific guidelines and most of the available literature seems to be flawed by critical issues. Given the wide heterogeneity and the multidimensional needs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 175 publications
0
5
0
Order By: Relevance
“…Specifically detailing psychological wellbeing, evaluated through the PWB-18 scale, statistically significant differences between sight-impaired and sighted women, in favor of the latter, were detected in the environmental mastery and self-acceptance dimensions, as well as in the total score. Since visual disability deeply and negatively impacts interaction with the surrounding environment and daily-life self-efficacy, such results simply reflect the specific impairment-related issues ( 4 ). Moreover, given that the visually impaired women adhering to the study were younger than their sighted counterpart, a lack of environmental experience and self-awareness could be ascribed also to the younger age ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically detailing psychological wellbeing, evaluated through the PWB-18 scale, statistically significant differences between sight-impaired and sighted women, in favor of the latter, were detected in the environmental mastery and self-acceptance dimensions, as well as in the total score. Since visual disability deeply and negatively impacts interaction with the surrounding environment and daily-life self-efficacy, such results simply reflect the specific impairment-related issues ( 4 ). Moreover, given that the visually impaired women adhering to the study were younger than their sighted counterpart, a lack of environmental experience and self-awareness could be ascribed also to the younger age ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it is well-known that visual impairment deeply impacts psychological, social, and physical functionality, thus hindering participation in daily-life, leisure, and sport activities ( 4 ). According to several studies, visually impaired people perceive and experience prejudices, barriers, accessibility issues, and restrictions in participation in a regular and structured physical activity throughout their lifespan ( 5 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the aforementioned evidence and applying an innovative perspective simultaneously oriented to daily life and sport performance improvement, the main focus of our adapted athletic training intervention was to promote the upper body functionality of BC survivors practicing dragon boating through a proprioceptive multimodal approach. Since trunk postural control and segmental coordination cannot be increased without reinforcing global body awareness, anatomofunctional prerequisites, and conditional skills [17,71,118,119], a total body circuit training methodology has been applied. The use of a biofeedback-based tool, purposely designed for proprioceptive quantitative evaluation/improvement [68], and a tailored exercise load progression allowed us to reach the main goal of our intervention taking into account the individual skills and fitness level of each participant.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that motor efficiency is strongly linked to the most archaic component of the proprioceptive system that can be productively stimulated and re-educated exclusively through a high-frequency proprioceptive input flow [70]. When variance is detected by the traditional tilting boards, the sensorized ones apply high-frequency signals able to train the subject to properly select and interpret them, thus progressively generating rapid and relevant sensorimotor responses [71,72]. Such a methodological approach also allows us to objectively evaluate the individual motor skills and consequently tailor each exercise aim/load to them [73,74].…”
Section: Introductionmentioning
confidence: 99%